Factors affecting productive traits in Gir crosses - U. Y. BHOITE, M. G. MOTE (Indian Journal of Animal Production and Management, 2020)
The data on milk production traits of FG (50% HF+50% Gir), IFG (interse 50% HF+50% Gir), FJG (50% HF+25% Jersey+25% Gir), IFJG (interse 50% HF+25% Jersey+25% Gir) and R (50% HF+12.50% Jersey+37.50% Gir) crosses of Gir maintained at R.C.D.P. on cattle, M.P.K.V., Rahuri were collected from year 1972 to 2015. The collected data were analysed for estimation of means of productive traits viz., lactation milk yield and 300 days milk yield by considering effects of period/season of calving by adopting least-square technique. The overall least squares means of lactation yield (kg) and 300 DMY (kg) in second lactation were 3860.68 ± 86.00 and 3682.39 ± 75.60 in FG, 3017.30 ± 60.60 and 2806.27 ± 47.20 in IFG, 3395.83 ± 78.82 and 3274.51 ± 76.22 in FJG, 3120.07 ± 59.16 and 2833.80 ± 45.52 in IFJG and 3475.91 ± 125.47 and 3104.53 ± 92.63 in R genetic group. The period of calving had significant effect on LMY and 300 DMY in FJG and IFJG groups. The season of calving had non-significant effect on lactation yield in all groups. The effect of season of calving on 300 DMY was non-significant in all groups in three lactations. The genetic group had significant effect on LMY and 300 DMY traits. FG halfbred performed better for productive traits over IFG, FJG, IFJG and 5/8 Gir crossbred.